Parasitic Flatworms: Molecular Biology, Biochemistry, Immunology and Physiology 2006
DOI: 10.1079/9780851990279.0348
|View full text |Cite
|
Sign up to set email alerts
|

Proteases in trematode biology.

Abstract: This chapter discusses the following topics: trematode gut, blood as a source of amino acids, prevention of ingested blood clotting in the gut, lysis of blood cells, peptidases involved in the digestion of blood and tissue proteins in schistosomes and liver flukes, regulation of the digestive process, non-feeding functions attributed to peptidases (invasion and migration through host tissue, excystment of juvenile parasites, hatching of eggs), phylogeny of proteases (cathepsin B, cathepsins L and F, aspartic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Recently Lowther et al (36) showed that members of the most predominant cathepsin L clade, FhCL1, have evolved an active site with a strong preference for hydrophobic amino acids, such as Leu, Ala, Phe, and Val, that are particularly abundant in hemoglobin (42%) indicating a specific adaptation for digestion of this protein. Hemoglobin is the prime supplier of amino acids that the parasites use in the anabolism of egg proteins, a major task because they produce 30 -50,000 eggs/day/worm (37). Members of the other major clade, FhCL2, have specific amino acid substitutions in the active site cleft that gives these proteases the ability to cleave substrates with Pro residues and facilitates the degradation of proline-rich interstitial collagen during the migration of the parasites through the tissues (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Lowther et al (36) showed that members of the most predominant cathepsin L clade, FhCL1, have evolved an active site with a strong preference for hydrophobic amino acids, such as Leu, Ala, Phe, and Val, that are particularly abundant in hemoglobin (42%) indicating a specific adaptation for digestion of this protein. Hemoglobin is the prime supplier of amino acids that the parasites use in the anabolism of egg proteins, a major task because they produce 30 -50,000 eggs/day/worm (37). Members of the other major clade, FhCL2, have specific amino acid substitutions in the active site cleft that gives these proteases the ability to cleave substrates with Pro residues and facilitates the degradation of proline-rich interstitial collagen during the migration of the parasites through the tissues (38).…”
Section: Discussionmentioning
confidence: 99%
“…Saposin-like molecules are likely secreted from granules within cells lining the parasite esophagus so that ingested red blood cells are lysed as soon as they enter the digestive track. Hydrolysis of released hemoglobin by the cathepsin L proteases then takes place in the acidic cecum (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prosegment is removed by catalytic cleavage following secretion into the parasite intestine to reveal an active mature protease (28). Our MS studies showed that all cathepsin L proteases secreted by adult F. hepatica lack the prosegment and are thus fully processed mature enzymes.…”
Section: Identification Of Adult F Hepatica Es Proteins By Nano-lc-ementioning
confidence: 99%
“…3. Despite the lack of conservation in this signature section, each still reserves an Asn residue and thereby retains a highly specific cleavage site for the trans-processing enzyme asparaginyl endopeptidase that initiates or "kick-starts" the enzyme activation process (28). Another highly conserved feature within the non-conserved C-terminal region of the prosegment is a Leu-Ser2His motif that we have shown is essential for autocatalytic cleavage between cathepsin L proteases once activation is initiated by the asparaginyl endopeptidase (20).…”
Section: Identification Of Adult F Hepatica Es Proteins By Nano-lc-ementioning
confidence: 99%